Geopolitične perspektive srbskega vprašanja na Balkanu - Zupančič, Jernej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2013)
The article is analyzing the geopolitical dimensions of Serbian ethnic question on the Balkans. The main attention is paid to the political-territorial development of the core of the Balkan space, where the role of Serbs as ethnic as well as political category was different through the whole modern period, but very important. Nowadays, the Serbs are a nation of multi-ethnic country and with many minorities and large diaspora. This situation makes the Serbian nation more vulnerable politically and contributes to the geopolitical liability of the Balkans.
Keywords: Balkan; Balkans; geopolitika; Jugovzhodna Evropa; politična geografija; Serbia; Srbija